Politainment News Framing of DPR RI Members Mulan Jameela on The Online Media - Fitria Ulfa Ulfa Fitria; Indah Suryawati (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
The success of Mulan Jameela to become members of the Indonesian Parliement 2019-2024 drew the attention of online media. However. Some online media deliberately package this event in the form of politainment news. This research aims to find out the news framing of Mulan politainment news when officially appointed as a member of the Indonesian Parliament 2019-2024. The research method used is the Framing Zhongdang Pan and Gerald M. Kosicki. Pan Kosicki's framing device is divided into four large structures : syntactic structure, script structure, thematic structure, and rhetorical structure. The object of the research was the news texts Mulan as members of the Indonesian Parliament in Tribunnews.com and Detik.com in the October 2019 period. The results showed that the cognitive tools used by Tribunnews.com and Detik.com in coding information and interpreting events about Mulan as members of the Indonesian Parliament are constructed differently. Okezone.com framing tends to benefit Mulan. While framing Tribunnews.com, Detik.com, Liputan6.com, dan Kompas.com tend to corner Mulan. Where the most highlighted side is the clothing choices used by Mulan, the legal cases faced and the endorsement that received the KPK response. While Mulan success in holding seats in the Indonesian Parliament 2019-2024 period is not so highlighted. Keywords: framing; news; online media; politainment